Recommended diagnostic criteria for paraneoplastic neurological syndromes. Issue 8 (16th July 2004) - Graus, F; Delattre, J Y; Antoine, J C; Dalmau, J; Giometto, B; Grisold, W; Honnorat, J; Smitt, P Sillevis; Vedeler, Ch; Verschuuren, J J G M; Vincent, A; Voltz, R
Abstract : Background: Paraneoplastic neurological syndromes (PNS) are defined by the presence of cancer and exclusion of other known causes of the neurological symptoms, but this criterion does not separate "true" PNS from neurological syndromes that are coincidental with a cancer. Objective: To provide more rigorous diagnostic criteria for PNS. Methods: An international panel of neurologists interested in PNS identified those defined as "classical" in previous studies. The panel reviewed the existing diagnostic criteria and recommended new criteria for those in whom no clinical consensus was reached in the past. The panel reviewed all reported onconeural antibodies and established the conditions to identify those that would be labelled as "well characterised". The antibody information was obtained from published work and from unpublished data from the different laboratories involved in the study. Results: The panel suggest two levels of evidence to define a neurological syndrome as paraneoplastic: "definite" and "possible" . Each level can be reached combining a set of criteria based on the presence or absence of cancer and the definitions of "classical" syndrome and "well characterised" onconeural antibody. Conclusions: The proposed criteria should help clinicians in the classification of their patients and the prospective and retrospective analysis of PNS cases.